2004
DOI: 10.1211/0022357022791
|View full text |Cite
|
Sign up to set email alerts
|

Human skin permeation of Δ8-tetrahydrocannabinol, cannabidiol and cannabinol

Abstract: The purpose of this study was to quantify the in-vitro human skin transdermal flux of Delta8-tetrahydrocannabinol (Delta8-THC), cannabidiol (CBD) and cannabinol (CBN). These cannabinoids are of interest because they are likely candidates for transdermal combination therapy. Differential thermal analysis and in-vitro diffusion studies with human tissue were completed for the compounds. Heats of fusion, melting points and relative thermodynamic activities were determined for the crystalline compounds, CBD and CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 21 publications
7
60
1
1
Order By: Relevance
“…Besides deposition from the environment, drug findings in hair from controlled studies also indicated a deposition from sebum and sweat or via the skin [4,41,42]. In in vitro studies, the horny layer exhibited some resistance to the diffusion of cannabinoids across human skin in the following order: THC < CBN < CBD [43,44]. The passage of a lipid-soluble compound from blood to other body fluids being dependent on the substance's pK a and pH, THC is not expected to accumulate in sweat.…”
Section: Discussionmentioning
confidence: 99%
“…Besides deposition from the environment, drug findings in hair from controlled studies also indicated a deposition from sebum and sweat or via the skin [4,41,42]. In in vitro studies, the horny layer exhibited some resistance to the diffusion of cannabinoids across human skin in the following order: THC < CBN < CBD [43,44]. The passage of a lipid-soluble compound from blood to other body fluids being dependent on the substance's pK a and pH, THC is not expected to accumulate in sweat.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous-Another route of cannabinoid exposure that avoids first-pass metabolism and improves THC bioavailability is topical administration [43]. Cannabinoids are highly hydrophobic, making transport across the aqueous layer of the skin the rate-limiting step in the diffusion process [44] [45].…”
Section: 14mentioning
confidence: 99%
“…Cannabinoids are highly hydrophobic, making transport across the aqueous layer of the skin the rate-limiting step in the diffusion process [44] [45]. In vitro diffusion studies may underestimate in vivo transdermal flux [43]. After application of a dermal patch, mean steady-state plasma concentration of Δ 8 -THC was 4.4 ng/ml within 1.4 h, and was maintained for at least 48 h. Permeabilities of CBD and CBN were found to be 10-fold higher than for Δ 8 -THC.…”
Section: 14mentioning
confidence: 99%
“…These results need to be considered carefully when conducting clinical trials where it is not ethically possible to cease pharmacotherapy of drugs metabolised by CYP enzymes. However, a novel route worth considering and which avoids the hepatic first pass is transdermal delivery (Stinchcomb et al, 2004).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%